2013
DOI: 10.1021/jf3052658
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profiles of Vitis davidii and Vitis quinquangularis Species Native to China

Abstract: The accumulation of phenolics in the skins of two Vitis davidii cultivars ('Ziqiu' and 'Xiangzhenzhu') and one Vitis quinquangularis cultivar ('Xiangshan No. 4') native to China was followed during ripening. It was found that the anthocyanin composition of all three grapes was dominated by anthocyanidin 3,5-O-diglucosides. The cultivar 'Xiangshan No. 4' (V. quinquangularis) contained a high level of 3',4'-substituted anthocyanins and low levels of flavonols and 3',4'-substituted flavan-3-ols, indicating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 38 publications
2
58
2
1
Order By: Relevance
“…This is considered a beneficial trend in the native V. davidii (“Ziqiu” and “Xiangzhenzhu”) and V. quinquangularis (“Xiangshan No. 4”) species in China (Liang et al, ). Flavonols from muscadine grapes have a qualitatively different pattern to the two V. vinifera studied here and comprised mostly of a series of 3′,4′,5′‐type flavonols followed by 3′,4′‐type (e.g., 44.8%–72.6% and 23.1%–40.1% of total flavonol in 2014, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This is considered a beneficial trend in the native V. davidii (“Ziqiu” and “Xiangzhenzhu”) and V. quinquangularis (“Xiangshan No. 4”) species in China (Liang et al, ). Flavonols from muscadine grapes have a qualitatively different pattern to the two V. vinifera studied here and comprised mostly of a series of 3′,4′,5′‐type flavonols followed by 3′,4′‐type (e.g., 44.8%–72.6% and 23.1%–40.1% of total flavonol in 2014, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, in our research, 3,5- O -diglucoside anthocyanins was the predominant anthocyanins in V. davidii . The studies have shown that, the 3,5- O -diglucoside anthocyanins were usually detected in other Chinese wild grapes [5, 7, 55, 56]. Therefore, the V. davidii was closer to the other Chinese wild grapes from the perspective of the composition of anthocyanins.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, the research of anthocyanins in Chinese wild grapes has been carried out, and the profile of anthocyanins in Chinese wild grapes is significantly different from V. vinifera [5, 7, 54–56]. Generally, only 3- O -monoglucoside anthocyanins are detected in V. vinifera cultivars, and almost all of the cultivars of V. vinifera are devoid of pelargonidin-based anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three groups of flavonoids were isolated from the grape skins according to Liang et al (2013). For the extraction of anthocyanins, grape skin powder (0.5 g) was suspended in 10 mL of methanol containing 2% (v/v) formic acid.…”
Section: Extraction Of Flavonoid Compounds From Grape Skinsmentioning
confidence: 99%